2016
DOI: 10.18203/2394-6040.ijcmph20161397
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hearing impairment among primary school children in rural and urban areas of Aligarh, Uttar Pradesh, India

Abstract: Ear diseases are particularly important in primary school children because it is the earliest time when they learn ABSTRACT Background: Hearing impairment in school children is particularly important because it is the earliest time when the foundation for education and mental and linguistic development is laid down. Present study aims at estimate the burden of hearing impairment among school children in rural and urban field practice areas of Urban and Rural Health Training Centers, JNMCH, AMU, Aligarh, Uttar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
5
1
Order By: Relevance
“…The present study results revealed a total of 75 (3.25%) children with hearing and otological problems which is similar to the study by Savithri et al 14 which reported 3.4% of prevalence rate for hearing disorders among school children and also a study by Varsha et al 16 who reported presence of hearing and otological problems in 85 children among 1453 school children. Further, among the 75 children with hearing and otological problems, 53 (2.30%) children were having otological problems such as impacted curemen, perforation, ear pain, etc which is lesser in contrast to the findings of previous studies by Chadha et al, 18 who reported a prevalence rate of 17.92% among school children in northern India and also a study by Parvez et al 20 who reported a prevalence rate of 17.9% among school children of Aligarh district. Further, the prevalence rates of hearing disorders was also lower compared to the study by Ojha et al 15 who reported a prevalence rate of 15.7% for hearing impairment in school children in the age range of 3-14 years.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…The present study results revealed a total of 75 (3.25%) children with hearing and otological problems which is similar to the study by Savithri et al 14 which reported 3.4% of prevalence rate for hearing disorders among school children and also a study by Varsha et al 16 who reported presence of hearing and otological problems in 85 children among 1453 school children. Further, among the 75 children with hearing and otological problems, 53 (2.30%) children were having otological problems such as impacted curemen, perforation, ear pain, etc which is lesser in contrast to the findings of previous studies by Chadha et al, 18 who reported a prevalence rate of 17.92% among school children in northern India and also a study by Parvez et al 20 who reported a prevalence rate of 17.9% among school children of Aligarh district. Further, the prevalence rates of hearing disorders was also lower compared to the study by Ojha et al 15 who reported a prevalence rate of 15.7% for hearing impairment in school children in the age range of 3-14 years.…”
Section: Discussioncontrasting
confidence: 60%
“…This may be attributed to otological disorders among children due to poor hygiene, the lack of awareness, literacy levels, socioeconomic status, lack of clinical facilities, etc among rural areas. 11,[17][18][19][20] Further, the prevalence of communication disorders was higher among males (2.38%) compared to females (1.91%) which may be due to differences in the developmental patterns of speech and language, 30 genetic and non-genetic factors where females are prone to overcome few of the developmental speech disorders such as stuttering 31,32,33 higher prevalence of otological conditions (trauma, middle ear infections, etc.) in males than females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8%) and multiple disorder (0.2%). Parvez A et al (2017)16 also reported prevalence rate of hearing impairment in (Uttar Pradesh, north India) school going children and result showed 17.9% (109/610) reported to have hearing impairment.Among the risk factors causing communication disorders, consanguinity was found to be the highest. Studies have reported higher number of consanguineous marriages in northern part of Karnataka compared to south.…”
mentioning
confidence: 97%